The APOEε3/ε4 Genotype Drives Distinct Gene Signatures in the Cortex of Young Mice - Foley, Kate E.; Hewes, Amanda A.; Garceau, Dylan T.; Kotredes, Kevin P.; Carter, Gregory W.; Sasner, Michael; Howell, Gareth R. (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Restrictions on existing APOE mouse models have impacted research towards understanding the strongest genetic risk factor contributing to Alzheimer’s disease (AD) and Dementia, APOEε4, by hindering observation of a key, common genotype in humans – APOEε3/ε4. Human studies are typically underpowered to address APOEε4 allele risk as the APOEε4/ε4 genotype is rare, which leaves human and mouse research unsupported to evaluate the APOEε3/ε4 genotype on molecular and pathological risk for AD and Dementia. METHODS: As a part of MODEL-AD, we created and validated new versions of humanized APOEε3/ε3 and APOEε4/ε4 mouse strains that, due to unrestricted breeding, allow for the evaluation of the APOEε3/ε4 genotype. As biometric measures are often translatable between mouse and human, we profiled circulating lipid concentrations. We also performed transcriptional profiling of the cerebral cortex at two and four months, comparing APOEε3/ε4 and APOEε4/ε4 to the reference APOEε3/ε3 using linear modeling and WGCNA. Further, APOE mice were exercised and compared to litter-matched sedentary controls, to evaluate the interaction between APOEε4 and exercise at a young age. RESULTS: Expression of human APOE isoforms were confirmed in APOEε3/ε3, APOEε3/ε4 and APOEε4/ε4 mouse brains. At two months, cholesterol composition was influenced by sex, but not APOE genotype. Results show that the APOEε3/ε4 and APOEε4/ε4 genotype exert differential effects on cortical gene expression. APOEε3/ε4 uniquely impacts ‘hormone regulation’ and ‘insulin signaling’, terms absent in APOEε4/ε4 data. At four months, cholesterol and triglyceride levels were affected by sex and activity, with only triglyceride levels influenced by APOE genotype. Linear modeling revealed APOEε3/ε4, but not APOEε4/ε4, affected ‘extracellular matrix’ and ‘blood coagulation’ related terms. We confirmed these results using WGCNA, indicating robust, yet subtle, transcriptional patterns. While there was little evidence of APOE genotype by exercise interaction on the cortical transcriptiome at this young age, running was predicted to affect myelination and gliogenesis, independent of APOE genotype with few APOE genotype-specific affects identified. DISCUSSION: APOEε4 allele dosage-specific effects were observed in circulating lipid levels and cortical transcriptional profiles, suggesting therapies aimed at modifying APOE biology to treat dementias may need to specifically target APOEε4 heterozygous and homozygous genotypes.